2001
DOI: 10.1074/jbc.m011488200
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Transcriptional Activation of HumanAcyl-coenzyme A: Cholesterol Acyltransterase-1 Gene by Interferon-γ and All-trans-Retinoic Acid THP-1 Cells

Abstract: cytokine that exerts many pro-atherosclerotic effects in vivo, causes up-regulation of ACAT-1 mRNA in human blood monocyte-derived macrophages and macrophage-like cells but not in other cell types. To examine the molecular nature of this observation, we identified within the ACAT-1 P1 promoter a 159-base pair core region. This region contains 4 Sp1 elements and an IFN-␥ activated sequence (GAS) that overlaps with the second Sp1 element. In the monocytic cell line THP-1 cell, the combination of IFN-␥ and all-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…While STAT-1 induction by IFNg is partially repressed by RA (red dotted line), the upregulation of TGFb-2 by RA is inhibited by IFNg. The dotted blue line depicts a presumptive pathway (Ulloa et al, 1999) (our unpublished data) that may account for the inhibition of TGFb-2 expression, which leads to the attenuation of the TGFb-2-dependent pathway (dotted green arrow) the one hand, IFNg and RA are naturally occurring biological agents with proven cell growth inhibitory and/or differentiating properties (Ho, 1985;Windbichler et al, 1996;Widschwendter et al, 1997;Chelbi-Alix and Pelicano, 1999;Guzhova et al, 2001;Yang et al, 2001;Hu et al, 2002). Moreover, our recent studies have indicated a differential expression of IFNg in pancreatic tumours, as opposed to the lack of detection in the normal pancreas (Andrianifahanana et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While STAT-1 induction by IFNg is partially repressed by RA (red dotted line), the upregulation of TGFb-2 by RA is inhibited by IFNg. The dotted blue line depicts a presumptive pathway (Ulloa et al, 1999) (our unpublished data) that may account for the inhibition of TGFb-2 expression, which leads to the attenuation of the TGFb-2-dependent pathway (dotted green arrow) the one hand, IFNg and RA are naturally occurring biological agents with proven cell growth inhibitory and/or differentiating properties (Ho, 1985;Windbichler et al, 1996;Widschwendter et al, 1997;Chelbi-Alix and Pelicano, 1999;Guzhova et al, 2001;Yang et al, 2001;Hu et al, 2002). Moreover, our recent studies have indicated a differential expression of IFNg in pancreatic tumours, as opposed to the lack of detection in the normal pancreas (Andrianifahanana et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IFNg and RA are well known for their ability to evoke a synergistic effect, which generally leads to an enhanced induction of target gene(s) and an exacerbation of the associated biological response(s). The impact of this synergism has been observed in a wide range of malignant tumour cell types, including breast, oral, neuroblastoma, leukemic and renal cancer cells (Ho, 1985;Windbichler et al, 1996;Widschwendter et al, 1997;Guzhova et al, 2001;Yang et al, 2001;Hu et al, 2002), but has remained largely unexplored in pancreatic tumour cells and, therefore, raises important questions.…”
Section: Introductionmentioning
confidence: 99%
“…signals elicited under various pathophysiologic conditions. The signals that up-regulate the expressions of ACAT1 in monocytes-derived macrophage include steroid hormones such as dexamethasone, interferon-␥, and vitamin D 3 Maung et al, 2001;Panousis and Zuckerman, 2000;Yang et al, 2001). In the future, it will be interesting to find out whether these or other agents can up-regulate the ACAT2 expression in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…We have produced the polyclonal antibody DM58 that specifically recognize the 56-kDa ACAT1 but not the 50-kDa ACAT1. Using antibodies DM58 and DM10 (which recognize both the 50-kDa ACAT1 and the 56-kDa ACAT1) as tools in parallel Western blots, thus far we are able to demonstrate the presence of the 56-kDa ACAT1 protein in PMA-activated THP-1 macrophages, and in human monocyte-derived macrophages; these cells express relatively abundant ACAT1 messages (33), (34). The 56-kDa ACAT1 may also be present in other human tissues and cells, and we are currently investigating this possibility in our laboratories.…”
Section: The 56-kda Acat1 Protein Can Be Recognized By Antibodies Prementioning
confidence: 99%